Effect of diurnal variations on cognitive and physical performance among female athletes - Gopal Chandra Saha; Bekir Erhan Orhan; Susmita Hazra; Subhashis Biswas; Prem Kumar Karak; Smriti Mondal; Shantanu Halder; Mahendra Pratap Gaur (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Objective: humans' circadian rhythm is an important parameter in understanding current biological, physiological, and psychological status, which broadly affects physical fitness. The physiological mechanisms underlying circadian rhythms remain underexplored despite their potential impact on physical and mental health. The study aims to examine the effect of diurnal variations on cognitive and physical performance in female athletes.